2015
DOI: 10.1007/s10705-015-9694-5
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of different organic amendments from agro-industrial wastes in organic lettuce crops

Abstract: An inadequate replacement of organic matter in agricultural lands progressively leads to soil fertility reduction and therefore, soil application of organic fertilizers and amendments should be promoted. The objectives of this 3-year research project on organic lettuce were to investigate the agronomic performance of experimental organic amendments obtained by using agro-industrial wastes in comparison with a commercial organic fertilizer, and to evaluate their short-term effects on soil mineral-N and soil org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…This result also suggests that no competition was determined by ASC in CS treatment. The comparable yield results of AD and ORG (in combination with both ES and CS), indicated that both are viable options for organic farmers, in agreement with other studies in Mediterranean area [14,15].…”
Section: Cauliflower and Tomato Agronomic Performancesupporting
confidence: 90%
“…This result also suggests that no competition was determined by ASC in CS treatment. The comparable yield results of AD and ORG (in combination with both ES and CS), indicated that both are viable options for organic farmers, in agreement with other studies in Mediterranean area [14,15].…”
Section: Cauliflower and Tomato Agronomic Performancesupporting
confidence: 90%
“…In fact, during the growing season there was an extreme adverse event, unusual in the experimental area, showing low mean month temperature (4.5 ‱ C) and several days of values below −4 ‱ C on January 2017, associated with high rainfall intensity (117 mm). The zucchini and lettuce marketable yields, which benefited from the residual fertility of the ASC, were comparable with other experimental results on organic crops production [29][30][31].…”
Section: Yield Performances and Energetic Outputsupporting
confidence: 87%
“…In addition, increasing the soil organic matter content improves the soil physical properties, such as structure and porosity, water retention and movement, and favors the establishment of carbon cycling (Gil et al 2008). Recently, Montemurro et al (2015) reported that different organic amendments from agro-industrial wastes improved soils and organic lettuce crops. Electrical conductivity reflects the total amount of dissolved ions available in the water or the salinity of the soil (Lim et al 2015a).…”
Section: Soil Propertiesmentioning
confidence: 99%